أهميّة المُصطلح وآليات توليده في اللُّغـــة العربـــــية - بوفلاقة, محمد سيف الإسلام (جامعة الوادي - University of Eloued, 2022)
يسعى هذا البحث إلى بيان أهمية المصطلح في الدراسات العلمية لدى القدماء والمحدثين، وإيضاح طرائق توليده في اللُّغة العربية، حيث إن الطرائق التي تتوالد بها المصطلحات ؛ لا تبتعد كثيراً عن الآليات المعروفة في اللُّغة العامة ،وعندما نتبصر في الدراسات اللّغوية العربيّة ، ونتأمل في الخطوط الرئيسة التي تم من خلالها إنتاج المصطلح في إطار البحث اللغوي؛ نجد أن طرائق توليده وصياغته ليست بعيدة عن توليد الكلمات، وينقسم البحث إلى قسمين رئيسين ، في القسم الأول سعى الباحث إلى إيضاح أهمية المُصطلح، وفي القسم الثاني تطرق إلى آليات توليد المُصطلح في اللُّغة العربية، وتوقف مع بعض مشكلات النقل والترجمة . This research aims to shed light on the role of linguistic planning in the advancement, development and development of the Arabic language; It also aims to highlight the relationship between language and linguistic planning, and addresses some issues related to linguistic and cultural security, and globalization that attacks its fierce attacks on the cultural and intellectual arena, and attempts to blur cultural specificities, and erase the cultural heritage, and the personal and private features that characterize it. The literature and art of each of the civilizations, and tries to tame them in one frame, and include them in a specific angle, thus addressing the aesthetics of diversity and cultural difference between the peoples and nations of the world, and this is what places researchers on the responsibility of promoting cultural and linguistic security; There are many conflicts between the theses of cultural discourses in every society that has an authentic cultural specificity; The conservative authentic is the one who protects and fortifies his language. In our contemporary time, a fierce desire to invade and invade the sites of national languages appears and looms on the horizon, and this is what makes us fear this sweeping invasion of the security of the existence of our national languages. Named: (Linguistic security), which cannot be embodied only by linguistic awareness; Rather, gigantic efforts must be made to confront these indiscriminate campaigns. Immunizing and protecting national languages has become a civilized necessity to repel intrusions, and a civil and fateful need that falls within the framework of preserving dignity, preserving sovereignty, identity, and belief. Linguistic alienation does not differ in any aspect from spiritual, psychological, physical, cultural, and economic alienation.
The Importance of the Term and the Mechanisms of its Generation in the Arabic Language
مقال
Keywords: أهمية ؛ المصطلح ؛ آليات ؛ اللّغة ؛ العربية; Importance; Terminology; mechanisms; Arabic Language.